2023
DOI: 10.1186/s12906-022-03819-3
|View full text |Cite
|
Sign up to set email alerts
|

Costs of traditional Chinese medicine treatment for inpatients with lung cancer in China: a national study

Abstract: Background Traditional Chinese Medicine (TCM) has long been a widely recognized medical approach and has been covered by China’s basic medical insurance schemes to treat lung cancer. But there was a lack of nationwide research to illustrate the impact of the use of TCM on lung cancer patients’ economic burden in mainland China. Therefore, we conduct a nationwide study to reveal whether the use of TCM could increase or decrease the medical expenditure of lung cancer inpatients in mainland China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…There is some relevant literature, such as a study from mainland China in 2023 that reported on medical expenses for lung cancer inpatients. Between 2010 and 2016, there were a total of 47,393 lung cancer inpatients, and the median annual total medical expenses (Western medicine + Chinese medicine) per patient for those receiving Chinese medicine therapy were 18,798 RMB (approximately NT$ 82,711) (Nie et al, 2023). This study included a total of 43,122 NSCLC patients from 2007 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…There is some relevant literature, such as a study from mainland China in 2023 that reported on medical expenses for lung cancer inpatients. Between 2010 and 2016, there were a total of 47,393 lung cancer inpatients, and the median annual total medical expenses (Western medicine + Chinese medicine) per patient for those receiving Chinese medicine therapy were 18,798 RMB (approximately NT$ 82,711) (Nie et al, 2023). This study included a total of 43,122 NSCLC patients from 2007 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has one of the highest fatality rates among malignant tumors in China ( 21 , 22 ). Compared with small cell lung cancer, NSCLC has a slow onset and growth rate but is generally found to be in an advanced stage at initial diagnosis and, therefore, very difficult to control and treat ( 23 - 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… 22 As opposed to offsetting the use of WM, TCM provided a complementary role while treating the patients. 23 In China, there were approximately 910 million visits to TCM medical and health service units across the country and 26 million in-patients treated annually. 24 TCM is not only applied in China but also overseas.…”
Section: Introductionmentioning
confidence: 99%